Biodistribution of adeno-associated virus serotype 9 (AAV9) vector after intrathecal and intravenous delivery in mouse - Schuster, Daniel J.; Dykstra, Jaclyn A.; Riedl, Maureen S.; Kitto, Kelley F.; Belur, Lalitha R.; McIvor, R. Scott; Elde, Robert P.; Fairbanks, Carolyn A.; Vulchanova, Lucy (Frontiers in Neuroanatomy, 2014)
Adeno-associated virus serotype 9 (AAV9)-mediated gene transfer has been reported in central nervous system (CNS) and peripheral tissues. The current study compared the pattern of expression of Green Fluorescent Protein (GFP) across the mouse CNS and selected peripheral tissues after intrathecal (i.t.) or intravenous (i.v.) delivery of equivalent doses of single-stranded AAV9 vector. After i.t. delivery, GFP immunoreactivity (-ir) was observed in spinal neurons, primary afferent fibers and corresponding primary sensory neurons at all spinal levels. Robust transduction was seen in small and large dorsal root ganglion (DRG) neurons as well as trigeminal and vagal primary afferent neurons. Transduction efficiency in sensory ganglia was substantially lower in i.v. treated mice. In brain, i.v. delivery yielded GFP-immunoreactivity (-ir) primarily in spinal trigeminal tract, pituitary, and scattered isolated neurons and astrocytes. In contrast, after i.t. delivery, GFP-ir was widespread throughout CNS, with greater intensity and more abundant neuropil-like staining at 6 weeks compared to 3 weeks. Brain regions with prominent GFP-ir included cranial nerve nuclei, ventral pons, cerebellar cortex, hippocampus, pituitary, choroid plexus, and selected nuclei of midbrain, thalamus and hypothalamus. In cortex, GFP-ir was associated with blood vessels, and was seen in both neurons and astrocytes. In the periphery, GFP-ir in colon and ileum was present in the enteric nervous system in both i.v. and i.t. treated mice. Liver and adrenal cortex, but not adrenal medulla, also showed abundant GFP-ir after both routes of delivery. In summary, i.t. delivery yielded higher transduction efficiency in sensory neurons and the CNS. The observation of comparable gene transfer to peripheral tissues using the two routes indicates that a component of i.t. delivered vector is redistributed from the subarachnoid space to the systemic circulation.